Filsafat Dalam Kancah Peradaban: Konstruktif Atau Destruktif? - Damyati, Akhmad Rofii (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2020)
It is fact historically that philosophy is familiar in literatures of civilization. Even in every stage of human’s history, philosophers have their contribution to civilization. Philosophical works as their magnum opus from one age to other ones also exist and become basis of human thought. It means, philosophy become inseparable element in a construction of a civilization. Yet the other fact shows us that philosophy is seen as “horrible” discipline of knowledge for some people because of their assumption that philosophy has a destructive aspect to human thought. This paper explores the role of philosophy in civilization as well as investigates what the main element of philosophy that can be used to construct or even to destruct a civilization is. In doing it, the worldview of Islam is used as a framework of thought.